DYNAMICS OF DISABLEMENT DUE TO ONCOLOGICAL DISEASES OF ABLE-BODIED PEOPLE - Жабо, Т.М. (World of Medicine and Biology, 2014)
Oncological diseases are very important medical and social problem. Invalidism among oncological patients is increasing, this number is on the second place after cardiovascular diseases. In this research an analysis of medical and social aspects of disablement was held. On the basis of structural and logical analysis taking into account the principles of consistency a graphological model of solving problems of invalidity by providing various types of assistance was created. With the help of content analysis the legal aspects of disablement were analyzed. Relying on extensive index a structure of disablement by common diseases was set. Dynamics of invalidism among adult people during 2008-2012 years was defined. A well-timed diagnostics of tumors will give an opportunity to held the radical complex treatment and will increase its effectiveness that will decrease level of primary disability caused by tumors in Ukraine.
Keywords: disablement; oncological diseases; dynamics; health indicators